ASPEK HUKUM DALAM PENGELOLAAN PRODUKSI MEDIA TELEVISI DAN FILM - Ferdinanda Ferdinanda (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2023)
Film and television works in the form of audio-visual media are the youngest fields of art compared to other branches of art. As with other sectors, in Indonesia itself regulations for art are also governed by rules and laws (laws), both in terms of production, distribution and consumption. Not to limit creativity, but these rules are enforced to protect consumers (art connoisseurs) and the artists themselves from misuse of works of art such as elements of pornography, copyright abuse and so on. This paper is a descriptive analysis supported by literature on television and film available in libraries and online media.